Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1145/1052812.1052820
|View full text |Cite
|
Sign up to set email alerts
|

The impact of residential broadband traffic on Japanese ISP backbones

Abstract: This paper investigates the effects of the rapidly-growing residential broadband traffic on commercial ISP backbone networks. We collected month-long aggregated traffic logs for different traffic groups from seven major ISPs in Japan in order to analyze the macro-level impact of residential broadband traffic. These traffic groups are carefully selected to be summable, and not to count the same traffic multiple times.Our results show that (1) the aggregated residential broadband customer traffic in our data exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 7 publications
3
29
1
Order By: Relevance
“…Previous work found that for consumers diurnal patterns start with activity in the morning, steadily increasing throughout the course of the day, with the height of activity starting in the early evening and lasting till midnight [19,17]. We see this same overall pattern in terms of the number of active DSL sessions, as shown in Figure 3.…”
Section: Dsl Session Characteristicssupporting
confidence: 76%
See 1 more Smart Citation
“…Previous work found that for consumers diurnal patterns start with activity in the morning, steadily increasing throughout the course of the day, with the height of activity starting in the early evening and lasting till midnight [19,17]. We see this same overall pattern in terms of the number of active DSL sessions, as shown in Figure 3.…”
Section: Dsl Session Characteristicssupporting
confidence: 76%
“…This unique vantage point provides a broad view of residential traffic, enabling more comprehensive and detailed characterizations than was possible in previous work, such as Cho et al's studies based on backbone traces [19,9,10], other work that examined specific applications like P2P-assisted content distribution [27] and Skype [7], or studies using active measurements [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many measurement studies have reported that the empirically observed value of q is very small [13,14].…”
Section: A Overview Of Oversubscription Calculusmentioning
confidence: 99%
“…In the physical layer of the NWGN, high scalability, fine granularity, and flexibility will be very important, in addition to increased network capacity [5], [6]. In the NWGN, optical channels of varying granularity, such as path/burst/packet in the time domain and narCopyright c 2011 The Institute of Electronics, Information and Communication Engineers row/wide/bundle in the spectral domain, should be used as a pool of physical layer resources depending on the application (i.e., provider-by-provider, service-by-service, and so on) [5].…”
Section: Photonic Technologies For the Nwgn Physical Layermentioning
confidence: 99%